Developing a Multicultural Language Learning Platform that Fosters Intercultural Competence through Asynchronous Virtual Exchange - Sharon Williams; Ryan Brown; Tasha Campbell (Yayasan Adra Karima Hubbi, 2026)
Rapid globalization has intensified the need for language learning environments that not only build linguistic proficiency but also promote intercultural competence. Conventional digital learning platforms often emphasize language skills while insufficiently addressing learners’ ability to interpret, negotiate, and appreciate cultural differences. This study aims to develop and evaluate a multicultural language learning platform that integrates asynchronous virtual exchange to foster intercultural competence among university students from diverse cultural backgrounds. The research employs a mixed-methods design, combining platform analytics, pre- and post-intercultural competence scales, and qualitative reflections collected from 142 participants across three countries. The platform features guided cultural tasks, peer-to-peer message exchanges, and reflective prompts designed to stimulate perspective-taking and intercultural awareness. Results indicate significant improvement in students’ intercultural sensitivity, especially in dimensions related to curiosity, empathy, and tolerance of ambiguity. Interaction logs revealed sustained engagement with asynchronous exchange tasks, while qualitative data showed that learners valued the opportunity to communicate across cultural boundaries without the pressures of real-time interaction. The findings demonstrate that asynchronous virtual exchange can effectively complement language instruction by facilitating deeper cultural reflection and more equitable participation among students with varying linguistic confidence levels. The study concludes that culturally responsive digital platforms can serve as powerful tools for integrating language learning with intercultural competence development. Future research should explore long-term behavioral changes, integration with formal curricula, and adaptations for multilingual learning contexts.